Adaptive evolution of Candida albicans through modulating TOR signaling - Yaling Zhang; Lianjuan Yang; Youzhi Zhao; Kang Xiong; Hao Cui; Tianxu Wang; Xiaoping Liu; Chang Su; Yang Lu (mBio)
ABSTRACT Candida albicans stably colonizes humans but is a major fungal pathogen that occupies a wide range of divergent niches within the host. Rapid and effective adaptation to dynamic and contrasting host niches is associated with its pathogenicity. Recent studies have focused on genome evolution implicated in adaptive processes. Here, we demonstrate that modulation of TOR signaling is a mechanism underlying adaptive evolution in C. albicans. Clinical isolates of C. albicans exhibited enhanced commensal fitness in competition with the lab reference strain SC5314, which could be attributed to the diminished GlcNAc-responsive hypha-associated transcription in the gut. In vitro passaging of clinical isolates confers a reduction in TOR signaling, which is detrimental to fitness attributes in evolved strains, including stress response, antifungal drug tolerance, as well as in vivo commensal fitness and invasive infection. This phenomenon is observed independent of strain background and passaging environment. Importantly, inhibition of TOR signaling by rapamycin suppresses the fitness advantage observed in clinical isolates relative to their in vitro passaged derivatives. Thus, C. albicans undergoes rapid evolution via modulating TOR signaling that enables this fungus to adapt to diverse host niches.IMPORTANCEPathogens must be proficient at adapting to their surroundings to survive in the face of a changing microenvironment in the host and cause disease. This is particularly important for commensal-pathogenic organisms such as C. albicans as this fungus colonizes and infects mammalian hosts. Previous studies have focused on genome evolution such as aneuploidies, accumulation of point mutations, or loss of heterozygosity. Here, we demonstrate that C. albicans undergoes rapid adaptive evolution via modulating the TOR pathway. Alterations in TOR activity underlie some evolved traits with important consequences for both host adaptation and pathogenicity in C. albicans. Such mechanisms of adaptive evolution may be exploited by other organisms.